(untitled) (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This article explores the interplay between Islamic teachings and local culture within the Bone Kingdom during the 19th century. It specifically investigates the challenges involved in integrating Islamic principles with indigenous customs. Employing a descriptive-analytical method and a qualitative approach, the study reveals a reciprocal relationship between Islam and local traditions in the kingdom’s social and political spheres. The inherently tolerant and adaptable nature of Islamic teachings facilitated their integration into the existing cultural framework. Religious scholars played a pivotal role in contextualizing Islamic doctrines within the Bone society, while customary and royal institutions were instrumental in aligning local norms and social practices with Islamic values. This synergy fostered a harmonious social order, positioning the Bone Kingdom as a model of multicultural coexistence. The findings suggest that the integration of Islam and indigenous customs was not merely a process of adaptation, but rather a dynamic formation of a distinct and enduring cultural identity.